PERTANGGUNGJAWABAN PIDANA KORPORASI DALAM TINDAK PIDANA PENCUCIAN UANG (MONEY LAUNDERING) DI INDONESIA - Ayu Leni Cahyarani, Ni Putu; Rai Setiabudhi, I Ketut; Tjatrayasa, I Made (Kertha Wicara : Journal Ilmu Hukum, 2015)
Corporate criminal liability in money laundering under Article 6 to Article 9 of the Law No. 8 of 2010 Concerning eradication and Prevention of Money Laundering. In these articles explain the imposition of criminal sanctions and the corporation itself. The void norm contained in Article 9, which is about the appropriation of corporate wealth, but the law does not explain who is authorized to make appropriation. Future building regulations better to fill the void that norm, with it has the purpose to understand and analyze each development arrangement as a corporate criminal offense of money laundering in Indonesia. The method used to solve this problem is to know the normative method of secondary file. The results in the Criminal Code that has not been set on the corporation as the subject of criminal law, Draft Criminal Code in 2013 has been identified as the subject of corporate criminal law, if there are flaws in the criminal can not be in the criminal law in the Criminal Code.
Keywords: Regulation, Corporations, Crime, Money Laundering